CD147 mediates the adsorption of influenza A virus on the cell surface through direct interaction with HA - Wang, Ting; Cao, Lei; Zhang, Yufei; Cheng, Chuxing; Mao, Haiying; Hu, Xiaotong; Sun, Xiaomei; Huang, Kun; Jin, Meilin (Frontiers in Cellular and Infection Microbiology, 2025)
The adsorption of avian influenza virus (AIV) initiates the viral lifecycle, determining host tropism and pathogenicity. In addition to the classical AIV receptor, auxiliary receptors also play important roles in viral adsorption, though these remains to be fully elucidated. In this study, we identified 25 avian membrane proteins that interact with H5N6 hemagglutinin (HA), one of which, CD147, was confirmed to play a crucial role in promoting AIV adsorption and replication through overexpression and knockout experiments in DF1 and A549 cells. As a highly glycosylated transmembrane protein, CD147 was further shown to directly bind to the HA receptor-binding domain via its extracellular immunoglobulin-like domains, independently of its glycosylation, thereby mediating viral adsorption. Moreover, AIV infection upregulated the hyperglycosylated form (HG-CD147), while glycosylation inhibitors reduced viral adsorption, highlighting the role of glycosylation in modulating CD147 function. Finally, disrupting the CD147-HA interaction with soluble proteins or monoclonal antibodies inhibited viral adsorption and replication. This study identifies CD147 as an adjuvant receptor that promotes influenza virus adsorption and provides a mechanistic foundation basis for developing broad-spectrum therapeutics targeting HA-host protein interactions.